Factors associated with the required level of positive airway pressure in patients with obstructive sleep apnea syndrome - Karakurt, Suleyman Emre; Ozcan, Kursat Murat; Ozcan, Muge; Karakus, Mehmet Fatih; Ensari, Serdar; Dere, Haci Huseyin (Annals of Medical Research, 2021)
Aim: To investigate the factors associated with the required level of positive airway pressure as determined by continuous positive airway pressure titration in patients with obstructive sleep apnea syndrome (OSAS).Materials and Methods: A total of 87 OSAS patients were included in the study. The patients were assigned to two groups (low-pressure and high-pressure) based on the positive airway pressure level they required. The groups were compared with respect to baseline clinical characteristics, Muller maneuver findings and polysomnography findings. Results: There were 54 patients in the low-pressure group and 33 patients in the high-pressure group. No significant differences were found between low-pressure and high-pressure groups in terms of mean age, mean body mass index and gender distribution (p>0.05). A statistically significant higher rate of two level obstruction was found in the high-pressure group than in the low-pressure group (p=0.004). Comparison of the groups with respect to polysomnography findings showed mean apnea-hypopnea index (AHI) values of 42.88±26.63 and 54.16±31.29, mean rapid eye movement (REM)-AHI values of 37.38±30.72 and 58.21±26.09 and mean supine-AHI values of 66.04±32.98 and 64.03±31.15 in the low-pressure group versus high-pressure group, respectively. The mean AHI and supine-AHI values were not significantly different between the groups (p>0.05) but the high-pressure group showed a significantly greater mean REM-AHI in comparison to low-pressure group (p=0.002).Conclusion: The number of obstruction levels determined by Muller maneuver and REM-AHI appear to be the prominent factors affecting the positive airway pressure level required in OSAS patients
Keywords: CPAP ventilation; polysomnography; sleep apnea